2015
DOI: 10.1111/jth.12890
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective cohort study comparing activated partial thromboplastin time versus anti‐factor Xa activity nomograms for therapeutic unfractionated heparin monitoring in pediatrics

Abstract: To cite this article: Trucco M, Lehmann CU, Mollenkopf N, Streiff MB, Takemoto CM. Retrospective cohort study comparing activated partial thromboplastin time versus anti-factor Xa activity nomograms for therapeutic unfractionated heparin monitoring in pediatrics. J Thromb Haemost 2015; 13: 788-94. Summary. Background: Unfractionated heparin (UFH) is widely used to treat thromboembolic disease, but monitoring in children is challenging. Both activated partial throm-boplastin time (aPTT) and anti-factor Xa activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Increased dosing is needed in neonates due to decreased levels of antithrombin, and in children less than 1 year of age due to increased heparin binding to non‐antithrombin proteins. UFH can be monitored using the activated thromboplastin time (activated partial thromboplastin [aPTT]) or antifactor Xa assay, although studies have shown increased time in the therapeutic range when using the antifactor Xa assay . Heparin‐induced thrombocytopenia (HIT) is a rare, but serious side effect, which occurs in 1–2% of children exposed to heparin due to the development of antibodies against platelet factor 4/heparin complex .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased dosing is needed in neonates due to decreased levels of antithrombin, and in children less than 1 year of age due to increased heparin binding to non‐antithrombin proteins. UFH can be monitored using the activated thromboplastin time (activated partial thromboplastin [aPTT]) or antifactor Xa assay, although studies have shown increased time in the therapeutic range when using the antifactor Xa assay . Heparin‐induced thrombocytopenia (HIT) is a rare, but serious side effect, which occurs in 1–2% of children exposed to heparin due to the development of antibodies against platelet factor 4/heparin complex .…”
Section: Treatmentmentioning
confidence: 99%
“…UFH can be monitored using the activated thromboplastin time (activated partial thromboplastin [aPTT]) or antifactor Xa assay, although studies have shown increased time in the therapeutic range when using the antifactor Xa assay. 44 Heparininduced thrombocytopenia (HIT) is a rare, but serious side effect, which occurs in 1-2% of children exposed to heparin due to the development of antibodies against platelet factor 4/heparin complex. 45 Treatment includes stopping all heparin products and starting a nonheparin anticoagulant.…”
Section: Unfractionated Heparinmentioning
confidence: 99%
“…33 However, bleeding rates of up to 24% were reported in critically ill children receiving unfractionated heparin and who were at increased risk of bleeding. 34,35 The current management of symptomatic bleeding associated with dabigatran has some similarities to that observed in patients taking VKA, such as the cessation of anticoagulant treatment and the use of supportive care guided towards hemodynamic stabilization. In addition, hemodialysis may represent an option to expedite the removal of systemic dabigatran.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Furthermore, several studies have also demonstrated discrepancies between the aPTT and the anti-Xa assay. [15][16][17] Assay issues aside, what is clear is that there is a high degree of interpatient and even intrapatient variability in dosing, further complicating management. 18 Furthermore, heparin therapy can result in HIT, a serious and, in pediatrics, often under-recognized phenomenon, which has the potential to lead to severe consequences in an already vulnerable population of patients.…”
Section: Heparinmentioning
confidence: 99%